Pengaruh Debt to Equity Ratio dan Return On Equity Terhadap Nilai Perusahaan Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di BEI Periode 2019 – 2023 - Agung Setiawan Al Mukmin, Agung Setiawan Al Mukmin; Sofiatul Chusnaini, Sofiatul Chusnaini (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Abstrak. Price Earning Ratio (PER) is a ratio that can be used as an indicator when you want to buy stocks when the stock price is cheap and sell them back when the price is more expensive than the purchase price. Meanwhile, the Dept to Equity Ratio (DER) is a ratio that can be used to measure how much a company is able to pay off its long-term debt, and Return on Equity (ROE) is a ratio that can be used to show the company's ability to score profits based on the amount of equity. This ratio shows how efficiently the company's equity use is in generating profits. This research method uses the multiple linear regression analysis method, which allows researchers to see the relationship between two independent variables (DER and ROE) to the bound variable (PER), this study uses a quantitative approach. The data sources used in this study are secondary data sources sourced from the financial statements of mining sector companies listed on the Indonesia Stock Exchange (IDX) such as balance sheets and income statements. The results showed that DER and ROE had an influence on the bound variable, namely PER.